Host Restrictive Factors Are the Emerging Storm Troopers Against Enterovirus: A Mini-Review - Huan, Chen; Qu, Xinglong; Li, Zhaolong (Frontiers in Immunology, 2022)
Enterovirus infection continues to be a global health problem. The lack of specific drugs and broad-spectrum vaccines means an urgent need to develop effective strategies against enteroviruses. Host restrictive factors are a class of intrinsic host antiviral factors that have been broadly defined and investigated during HIV infections and have great significance for drug development and treatment design. In recent years, the essential role of host restrictive factors in regulating enteroviral infections has been gradually recognized and investigated. An increasing number of studies have shown that host-restrictive factors regulate multiple steps in the life cycle of enteroviruses. This mini-review discusses the restrictive factors against enteroviruses, their antiviral mechanism, and the arms race between them and enteroviruses. We also summarise the pathways that enteroviruses use to impair host antiviral signals. This mini-review characterizes the essential role of host restriction factors in enterovirus infections, which provides ideas and potential targets for antiviral drug design by regulating host restrictive factors. It also reveals potential future research on the interplay between host restrictive factors and enteroviruses.